Employee Performance Achievement Through application of principles “the right man in the right place” in organizational structure at the foundation miftahussalam islamic education Medan - Henny Purnama Dewi (Institute of Computer Science (IOCS), 2021)
Employees have a major role in every organizational activity, because employees become planners, actors, and determinants of the realization of organizational system goals. Organizational goals will be easier to achieve if employees are placed in positions that match their competencies. Therefore, it is very necessary to have a good organizational structure where in the organizational structure one of the management principles is applied, namely